Improving the rate of Patient Feedback for a Later Life Mental Health Liaison Team. Issue 1 (9th June 2016) - Cooper, Daniel
Abstract : It is well established that patient feedback is key to service development and improvement in the modern NHS. Certain patient groups can be particularly difficult to get feedback from, including those with dementia. The Later Life Mental Health Liaison Team at the Bristol Royal Infirmary were consistently receiving very low levels of patient feedback, such that it was insufficient to properly contribute to future service development and improvement. This QIP aimed to increase this level of feedback to a target of 15% from an existing average of 3%. The intervention centred around getting feedback from patients face to face and was developed over a number of PDSA cycles. The feedback questions were based upon the NHS Friends and Family Test. Over four PDSA cycles levels of feedback increased to 21% which more than achieved the goal set out at the start. This was however achieved at a time cost and involved an increased success rate of existing systems as well as new ones put into place by the QIP.